Analysis of Business Feasibility of Banana Chips on CV. Nikilo Kecamatan Bumiaji Kota Batu Malang - Ruswaji; Puguh Cahyono (Enrichment : Journal of Management, 2021)
This research was conducted at UD. Nikilo, Bumiaji Subdistrict, Batu City Malang, as one of the banana chips agro-industry business groups under the Integrated Business Service Center (PLUT) of Batu City Malang. This study aims to analyze the feasibility of the banana chips business at CV. Nikilo, Bumiaji District, Batu City Malang. The data analysis method used in this study is to use the cost and benefit analysis formula. Meanwhile, to calculate Business Feasibility, the formulas used are, Revenue Cost (R / C), Benefit Cost Ratio (B / C), and Return On Investment (ROI). The results showed that the average income in the banana chips business group assisted by PLUT Kota Batu Malang was Rp. 31,770,000.00 / month with production costs incurred of Rp. 21,604,000.00 / month. The production costs consist of a fixed cost of Rp. 6,481,250.00 and variable costs of Rp. 15,122,750.00 / month. From the results of data analysis, it was found that the benefits obtained in the banana chips agroindustry CV. Nikilo for Rp. 10,166,000.00 / month. Based on the calculation of business feasibility (R / C) Ratio, which is the ratio between revenue and total costs, the value (R / C) is 1.47 or 1.47> 1. (B / C) Ratio, namely the ratio of profits to total production costs that are more greater than zero, which has a ratio of 0.47 or 0.47> 0. Based on the comparison of profit and production capital, the ROI value is 11%. So it can be concluded that the agro-industry business of CV. Nikilo, Bumiaji District, Batu City Malang can be said to be profitable and feasible to run.